Improvement of indoor air quality using local fabricated activated carbon from date stones - Radaideh, J.A.; Alazba, A.A.; Amin, M.N.; Shatnawi, Z.N.; Amin, M.T. (Universiti Kebangsaan Malaysia, 2016)
Indoor air quality assessment in residential areas of Al-Hofuf city/Eastern region of Saudi Arabia is investigated through a multi-week multiple sites sampling survey. Critical air pollution indicators, including nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO), carbon dioxide (CO2) and total volatile organic compounds (TVOC) as well as temperatures were measured and analyzed during the study period from January to May 2014. Three site-types - roadside, urban and rural - were selected and within each site type, six locations were selected to study the varying indoor/outdoor air quality. The results indicated that NO2 and CO concentrations increased at the starting hours of the day. SO2 concentrations were relatively low and constant. In addition, a strong association between outdoor and indoor air quality was found. Measurements showed that indoor/outdoor ratio for TVOC ranged from 0.8 to 0.99. For CO2, NO2 and SO2, this was 0.92-1.15, 0.5-0.7 and 0.52-0.9, respectively. Finally, the effects of activated carbon (AC) were investigated to assess the extent of the improvement in the indoor air quality. The analysis of data obtained indicated that using locally prepared AC from date stones was an effective way to reduce the indoor air pollution with an overall efficiency of 85.5, while the use of industrial granular AC reduced the air pollutants with an efficiency of less than 0.6. In addition, AC was exposed to an exhaust gas flow to evaluate its elimination potential for high concentrated pollutants. The obtained results demonstrated that AC was also functioning as an efficient absorbent with an overall removal efficiency of 77.8%, even when it was exposed to high concentrations.